2015
DOI: 10.1016/j.engstruct.2014.11.015
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian approach for NDT data fusion: The Saint Torcato church case study

Abstract: This paper presents a methodology based on the Bayesian data fusion techniques applied to non-destructive and destructive tests for the structural assessment of historical constructions. The aim of the methodology is to reduce the uncertainties of the parameter estimation. The Young's modulus of granite stones was chosen as an example for the present paper. The methodology considers several levels of uncertainty since the parameters of interest are considered random variables with random moments. A new concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…From the previous studies on the application of the Bayesian framework to the assessment of existing buildings, it can be observed that, to the authors' knowledge, no applications to the assessment of masonry buildings can be found (with the exception of Ramos et al 2015, using however a masonry church as a case study). It can be noted that, in previous studies, the calibration of new values of confidence factors was performed based on the results of the analysis of a limited number of buildings.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…From the previous studies on the application of the Bayesian framework to the assessment of existing buildings, it can be observed that, to the authors' knowledge, no applications to the assessment of masonry buildings can be found (with the exception of Ramos et al 2015, using however a masonry church as a case study). It can be noted that, in previous studies, the calibration of new values of confidence factors was performed based on the results of the analysis of a limited number of buildings.…”
Section: Introductionmentioning
confidence: 87%
“…More recently, Bayesian inference was used to combine the results of different types of tests to reduce the uncertainty of the parameter estimation (e.g. Giannini et al 2014 for concrete strength, Ramos et al 2015 for the elastic modulus of a historical masonry building). In other works, Bayesian updating was used to correct the available capacity models for structural components based on experimental observations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach is generally not sensitive to local incipient defects, such as delamination. Non-destructive evaluation techniques [10][11][12][13][14][15], such as conventional ultrasonic techniques, have been used for safety inspection of a wide range of structures.…”
Section: Overviewmentioning
confidence: 99%
“…However, the ultrasonic pulse velocity in reinforced concrete is significantly affected by the presence of steel reinforcement, and this can impair significantly the results [1,3,4]. It is worth mentioning that, because of its versatility, the ultrasonic pulse velocity test can also be used in rocks to evaluate its mechanical properties, e.g., for structural diagnosis of old rock masonry of historical heritage building [14]. Likewise, the surface hardness test (type-L) can also be used to estimate the compressive strength in rocks for the same purpose.…”
Section: Introductionmentioning
confidence: 99%